STATUS SUMBERDAYA IKAN PELAGIS KECIL DAN FAKTOR PENENTU EFISIENSI USAHA PERIKANAN DI PANTAI UTARA JAWA - I Nyoman Suyasa; M. Fedi A. Sondita; Victor P.H. Nikijuluw; Daniel R. Monintja (Buletin PSP, 2007)
Fisheries activities in Northern coast of Java, mainly small pelagic fisheries, have an important role in fisheries development in Indonesia. This research was conducted in September 2005 - January 2006 and designed to identify the status of small pelagic fish resources and determinant factors promoting fisheries efficiency. The fisheries was at over-fished stage as attribute by decreasing annual productivity, from about 108.92 ton in 1995 to 43.39 ton in 2004. The significant factors promoting the production included size of fishing boat, duration of fishing trip, level of experiences of fishermen and type fishing gear. Meanwhile, significant factors promoting business success (profit) was price of fuel (locally known, solar). The efficiency of production was 0.52 – 0.55 and the profit of capture fisheries business was around 0.36 – 0.38 respectively.